2018
DOI: 10.12669/pjms.344.15681
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of traumatic dental injuries among preschool children with Autism Spectrum Disorder

Abstract: Objective:To determine the occurrence of traumatic dental injuries (TDIs) among Saudi preschool children with autism spectrum disorder (ASD) and compare it with Saudi preschool children without ASD.Methods:This study was conducted on a randomly selected sample of three to five year old Saudi preschool children in Riyadh, Saudi Arabia. The sample consisted of two groups; a study group (SG) of 257 ASD children, and a control group (CG) of age- and gender-matched 257 children without ASD. Clinical examinations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…All articles were classified as case‐control studies. In the study sample representative section, some studies showed major problems for the source of sample and minor problems in sampling method . No problems in sample size were found in six studies, and some studies showed major problems in entry criteria's/exclusions …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…All articles were classified as case‐control studies. In the study sample representative section, some studies showed major problems for the source of sample and minor problems in sampling method . No problems in sample size were found in six studies, and some studies showed major problems in entry criteria's/exclusions …”
Section: Resultsmentioning
confidence: 98%
“…Data from records and reports of those responsible were also used as a diagnostic criteria. The prevalence of TDI in patients with SN varied from 4.13% to 68.2% . For the control group, the prevalence of trauma ranged from 1.7% to 44.7% …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%